Effect of blood contact and saline solution on volume change and solubility of MTA HP Repair®, Bio-C Repair®, MTA Flow® and Bio-C Repair+® (Research, Society and Development, 2021)
The aim of the present study was to evaluate the effect of contact with blood and saline on the change in volume and solubility of calcium silicate cements MTA HP Repair®, Bio-C Repair®, MTA Flow® and Bio-C Repair ION+®.  After inserting the materials into retrograde cavities, they were scanned using a microtomograph 1174 (T0), and then placed in contact with blood and saline. After 07 days of contact, the specimens were scanned again (T01), and the volume change and was analyzed. The data were submitted to statistical analysis using the WILCOXON, MAN WHITNEY and KRUSKAL-WALLIS tests (p